51st AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2013
DOI: 10.2514/6.2013-860
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of a Supersonic Turbulent Flow in a Square Duct

Abstract: In this paper we have confirmed that eddy viscosity turbulence models are inadequate to predict secondary vortical flows developed from corners in internal flows. To remedy this shortcoming, we have added the quadratic constitutive relation (QCR) of Spalart to the one-and two-equation SA and SST turbulence models, respectively. The results of QCR with the SA and SST turbulence models have been validated against experimental data of Davis and Gessner for supersonic flow through a square duct. The approach is sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 4 publications
1
48
0
2
Order By: Relevance
“…However, it has been reported that this new term can lead to unstable results in finite volume solvers, 53 especially grids with mixed elements. 50 For such situations, C cr2 should be set to zero, as corner flow is dominated by the C cr1 term. OVERFLOW includes QCR2000, but the current release of US3D does not include either form of QCR.…”
Section: Ivd Quadratic Constitutive Relationmentioning
confidence: 99%
“…However, it has been reported that this new term can lead to unstable results in finite volume solvers, 53 especially grids with mixed elements. 50 For such situations, C cr2 should be set to zero, as corner flow is dominated by the C cr1 term. OVERFLOW includes QCR2000, but the current release of US3D does not include either form of QCR.…”
Section: Ivd Quadratic Constitutive Relationmentioning
confidence: 99%
“…15,35,36 The implementation of these models is that of OVERFLOW, with the 2.2k version coding used, and the SST model checked directly against the TMR website 15 to ensure that its implementation was consistent with what had been verified earlier. 37 …”
Section: Iib3 Turbulence Modelsmentioning
confidence: 99%
“…The Reynolds normal stresses (τ t,11 , τ t, 22 and τ t,33 ) are the main terms of the Reynolds stress tensor concerning intensity. Figure 5 shows that both RANS simulations ( Fig.…”
Section: Reynolds Normal Stressesmentioning
confidence: 99%
“…The version we implemented is the modified one from Mani [22] in order to take into account the compressible part, given that Turb'Flow is a compressible solver:…”
Section: Reynolds-averaged Navier-stokesmentioning
confidence: 99%